2008
DOI: 10.1002/clc.20165
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Hemorrhage: Precipitating Event for a Tako‐tsubo‐like Cardiomyopathy?

Abstract: There have been some reports in medical literature of patients with profound, reversible left‐ventricular (LV) dysfunction after sudden emotional stress. Originally, in Japan, the pattern was called tako‐tsubo cardiomyopathy. ST‐segment elevation is seen with this syndrome, and it may look like acute ST‐elevation myocardial infarction. However, it has also been well established that a subarachnoid hemorrhage can manifest with cardiac abnormalities. The authors describe a case involving a cerebral hemorrhage an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 26 publications
(26 reference statements)
0
17
0
1
Order By: Relevance
“…This assumption is also supported by our data, showing a higher frequency of diabetes mellitus, hypercholesterolemia, smoking and coronary artery disease in ischemic stroke patients as opposed to ICH patients (data not shown). In contrast, neuronally induced autonomic cardiac dysfunction, as reported in subarachnoid hemorrhage and ICH for stress-induced cardiomyopathy, might be a rarer event [18,19,20]. Another study from Hays and Diringer [21] identified elevated troponin I levels to be independently associated with in-hospital mortality after ICH; however, only 3 out of 90 deaths were related to cardiac events.…”
Section: Discussionmentioning
confidence: 99%
“…This assumption is also supported by our data, showing a higher frequency of diabetes mellitus, hypercholesterolemia, smoking and coronary artery disease in ischemic stroke patients as opposed to ICH patients (data not shown). In contrast, neuronally induced autonomic cardiac dysfunction, as reported in subarachnoid hemorrhage and ICH for stress-induced cardiomyopathy, might be a rarer event [18,19,20]. Another study from Hays and Diringer [21] identified elevated troponin I levels to be independently associated with in-hospital mortality after ICH; however, only 3 out of 90 deaths were related to cardiac events.…”
Section: Discussionmentioning
confidence: 99%
“…TTS following an ICH has been reported in nine cases so far [29,97,[120][121][122][123][124][125][126]. In four of these cases TTS was associated with cerebellar hemorrhage [29,97,125,126].…”
Section: Intra-cerebral Hemorrhage (Ich)mentioning
confidence: 92%
“…TKS-like reversible acute heart failure has also been reported to occur in patients with pheochromocytoma [14-16]. High dose catecholamine is known to be toxic to myocardial cells [14], and it has been suggested that the higher adrenergic receptor density in the apex versus the base of the heart accounts for differential injury leading to the characteristic “ballooning” of the left ventricular apex seen on cardiac imaging [1,17,18]. The complex pathophysiology of TKS also involves elements of coronary microvascular impairment, decreased endothelial nitric oxide production, and obstruction of left ventricular outflow, though theories suggest that an initial catecholamine flood is the trigger and greatest contributor to the disease process [19].…”
Section: Mechanisms Of Injurymentioning
confidence: 99%